2005
DOI: 10.1007/s10482-005-3872-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin of (−)-Geosmin on Grapes: On the Complementary Action of Two Fungi, Botrytis Cinerea and Penicillium Expansum

Abstract: One of the consequences of rot on grapes is the development of volatile compounds giving fungal, mouldy or earthy odours. Among these compounds, (-)-geosmin (trans-1,10-dimethyl-trans-9-decalol), a powerful aromatic compound with an earthy smell is a persistent defect in grape juice and wines made with at least partially rotten grapes. A microbiota analysis of rotten grapes containing (-)-geosmin was carried out on sites from four French regions from 1999 to 2002, to clarify the involvement in geosmin appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…Moreover, the Oscillatoria found in sediments has been observed not to produce geosmin in vitro. In addition to actinomycetes, fungi are generally predominant in terrestrial environments (Zaitlin and Watson, 2006), and some genera, such as Penicillium, Aspergillus and Botrytis (La Guerche et al, 2005;Dionigi and Ingram, 1994;Bö rjesson et al, 1993), have also been shown to produce geosmin and/or 2-MIB in the food industry. But no evidence shows that they are the dominant geosmin/2-MIB producers in water bodies.…”
Section: Isolation and Identification Of Odor-producing Actinomycetesmentioning
confidence: 99%
“…Moreover, the Oscillatoria found in sediments has been observed not to produce geosmin in vitro. In addition to actinomycetes, fungi are generally predominant in terrestrial environments (Zaitlin and Watson, 2006), and some genera, such as Penicillium, Aspergillus and Botrytis (La Guerche et al, 2005;Dionigi and Ingram, 1994;Bö rjesson et al, 1993), have also been shown to produce geosmin and/or 2-MIB in the food industry. But no evidence shows that they are the dominant geosmin/2-MIB producers in water bodies.…”
Section: Isolation and Identification Of Odor-producing Actinomycetesmentioning
confidence: 99%
“…The distribution of the microbiota associated with rotten grapes containing geosmin was studied on different sites (La Guerche et al , 2005b. Some microorganisms commonly present on grapes were isolated (Hewitt 1994, Serra et al 2005: fungi, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Attacks can reduce grape yield, as well as wine quality, by causing off-flavours, unstable colour, oxidative damage, premature ageing and difficulties in clarification (Ribereau-Gayon, 1983;Smart & Robinson, 1991). Furthermore, berries infected by B. cinerea can readily be invaded by other fungi, such as Penicillium expansum, which further favours the risk of off-flavour development (Smart & Robinson, 1991;La Guerche et al, 2005).…”
Section: Introductionmentioning
confidence: 99%